PERANAN PASTRY SECTION DALAM MENUNJANG OPERASIONAL PELAYANAN DI RESTORAN HOTEL GRAND JATRA PEKANBARU - Ayu, Diana Mutiara; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Role of Pastry Section in Supporting Service Operations at Grand Jatra Hotel Restaurant Pekanbaru is based on the fact that the pastry section or bread and cake section in the hotel has an important role in supporting service operations in the hotel restaurant. The Pastry section is responsible for producing bread, cakes, and other bakery products that are an important part of the food and beverage menu at the hotel restaurant. This study aims to determine the role of the pastry section in supporting service operations at the Grand Jatra Hotel Pekanbaru restaurant along with the obstacles faced by the party section in supporting service operations at the Grand Jatra Hotel Pekanbaru restaurant. The theories used are product quality theory, operational standard theory, recipe standard theory, pastry section theory, superior product theory, hotel revenue theory, and employee training theory. The type of research taken by researchers is qualitative descriptive. The research data collection stage is to conduct a face-to-face interview process with the speakers, observation and documentation, observations and conversation results analyzed by the researcher, namely 5 (five) resource persons consisting of Executive chef, Chef the partie, Demi Chef, pastry staff, pastry intern. The result of this study is The role of the pastry section in supporting service operations at the Grand Jatra Pekanbaru hotel restaurant shows that the Pastry section plays an important role in supporting service operations at the Grand Jatra Pekanbaru Hotel Restaurant. Good hotel management involves a combination of work between departments that support and complement each other so that hotel revenue increases thanks to the products produced. Keywords: Pastry section, Role, product quality, operational standards, recipe standards, superior products, employee training Hotel Gand Jatra Pekanbaru